Trapping a dark soliton pulse within a nano ring resonator - Charoenmee, A.; Pornsuwancharoen, N.; Yupapin, P. P. (My University, 2010)
We propose the interesting results that a dark soliton pulse can be localized within a nonlinear nano-waveguide. The system consists of nonlinear micro and nano ring resonators, whereas the dark soliton can be input into the system and trapped within the nano-waveguide. A dark soliton pulse is input into a ring resonator and chopped to be the smaller pulses. The required pulse is filtered and amplified, which can be controlled and localized within the nano-waveguide. The localized bright soliton is also reviewed and discussed. © 2009 Elsevier GmbH. All rights reserved.
Keywords: Dark soliton; Optical memory; Stopped light; Stored light